Simplifique a expressão (x – y)2 – (x + y)2
Soluções para a tarefa
Respondido por
44
(x – y)² – (x + y)² =
(x² – 2xy + y²) – (x² + 2xy + y²) =
x² – 2xy + y² – x² – 2xy – y² =
x² – x² – 2xy – 2xy + y² – y² =
– 4xy
Espero ter ajudado.
Bons estudos.
(x² – 2xy + y²) – (x² + 2xy + y²) =
x² – 2xy + y² – x² – 2xy – y² =
x² – x² – 2xy – 2xy + y² – y² =
– 4xy
Espero ter ajudado.
Bons estudos.
Respondido por
9
(x-y)² -( x+y)²= x² -2xy +y² - (x² + 2xy +y²)= x² -x² -2xy -2xy +y²- y²= - 4xy
Perguntas interessantes
Geografia,
7 meses atrás
Matemática,
7 meses atrás
Português,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás